The Spatial Consequences of High-Rise Building of The Public Space of Basuki Rahmat Corridor, Surabaya - Annisa Budhiyani Tribhuwaneswari; Endang Titi Sunarti Darjosanjoto; Murni Rachmawati (Institut Teknologi Sepuluh Nopember, 2015)
High-rise building functioned as a reflection of the city growth toward modernism. It indicated changes for more advanced urban development, showing the quality at various section, such as tourism, economy, and its environment. The rapid growth of vertical building creating an effect towards the surrounding environment, the public space, which need to be acknowledged and evaluated. The research method applied to the study was descriptive qualitative, mainly focused at analyzing the spatial consequences of high rise building upon the public space of Basuki Rahmat Corridor, Surabaya. The data was presented by index card and analyzed by using synchronic reading techniques. The results shows that there is relation and linkage between the public space and the high-rise building at the corridor.